2015
DOI: 10.1021/acs.macromol.5b00327
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Lubrication: The Macromolecular Domain

Abstract: Macromolecules, which adsorb or intrinsically form boundary layers at surfaces sliding past each other in aqueous media, are ubiquitous both in technology and in biological systems and can form effective boundary lubricants. Over the past decade or so, hydration layersrobustly bound water molecules that surround charges or zwitterionic groups of different macromolecular specieshave been identified as remarkable lubricating elements, sustaining high loads while exhibiting a fluid-like response to shear with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(96 citation statements)
references
References 160 publications
3
93
0
Order By: Relevance
“…This lubrication mechanism was emphasized and discussed in two seminal publications by Raviv, Klein and Laurat, 45,46 and more recently in a perspective article by Jahn and Klein. 47 The double-chained cationic surfactant didodecyldimethylammonium bromide adsorbs strongly onto the highly negatively charged mica surface to form a bilayer structure. In SFA experiments it has been demonstrated that this surfactant bilayer has sufficient cohesion to withstand shear under high loads, and the friction force was found to be so small that it could not be measured with the very accurate and sensitive SFA tribometer.…”
Section: Amphiphilic Moleculesmentioning
confidence: 99%
“…This lubrication mechanism was emphasized and discussed in two seminal publications by Raviv, Klein and Laurat, 45,46 and more recently in a perspective article by Jahn and Klein. 47 The double-chained cationic surfactant didodecyldimethylammonium bromide adsorbs strongly onto the highly negatively charged mica surface to form a bilayer structure. In SFA experiments it has been demonstrated that this surfactant bilayer has sufficient cohesion to withstand shear under high loads, and the friction force was found to be so small that it could not be measured with the very accurate and sensitive SFA tribometer.…”
Section: Amphiphilic Moleculesmentioning
confidence: 99%
“…[1a, 2] These tightly bound water molecules render the polyelectrolyte chains highly swelled in water, [2,3] and are believed to be the major mechanism for their promising applications such as underwater oil repellency, [4] antifouling, [1b, 5] oil/water separation, [6] and lubrication. [7] Of all polyelectrolytes,t he zwitterionic ones exhibit excellent hydrophilicity and hydration strength by integrating both positive and negative ionic groups. [1a, 8] Upon contact with hydrophobic oil, the polyelectrolyte surfaces,l ike most polar surfaces with high surface energy, will reorient their ionic groups inwards to lower the surface free energy,l eading to evident loss of surface hydrophilicity and wettability alteration.…”
mentioning
confidence: 99%
“…
and investigated the fl uidity of hydration layers [26][27][28] to better understand the frictional behaviors in biological systems. Previously, our group reported different kinds of liquid superlubricity, e.g., boric acid with glycerol, [ 29 ] phosphoric acid, [ 30 ] as well as glycerol, [ 31 ] polyhydroxy alcohol solutions, [ 32 ] ethylene glycol, [ 33 ] and silicone oil [ 34 ] by running-in with an acid solution.
…”
mentioning
confidence: 99%